MONITORING SISTEM BERBASIS WEB KEAMANAN TRANSAKSI PENGIRIMAN UANG PADA PENYELENGGARA TRANSFER DANA DENGAN MENGGUNAKAN PERATURAN BANK INDONESIA ANTI PENCUCIAN UANG & PENCEGAHAN PENDANAAN TERORISME - Rahmat Rian Hidayat; Dwiki Jatikusumo (Sekolah Tinggi Teknik - PLN, 2019)
PT BETANET as Non-Bank Fund Transfer Provider has an obligation to comply the provisions of 19/10 / PBI / 2017 concerning about Anti-Money Laundering and Combating the Financing of Terrorism and the Proliferation of Weapons of Mass Destruction. (AML/CFTWMD) for Non-Bank Payment System Service Providers and Non-Bank Foreign Currency Exchange Business Operators. Having Remittance partners abroad and Domestic transactions with an average of 50 thousand transactions per month, BETANET must have a special AML & CFT unit to ensure that fund transfer activities are complies with the PBI about AML & CFT. The duties of the AML & CFT Unit are routinely ensure that funds transfer transactions which are deemed suspicious or not. The parameter of suspicious transaction has been set out in the policy. However, the current conditions of BETANET, it does not have a monitoring system which is integrated with the Host Remittance System. It means that the AML & CFT activities are still carried out manually every day, so that it will create several risks such as Operational risk, Reputation risk, Legal risk. Judging from these conditions and problems, this study will propose to build a security system for web-based fund transfer transactions. Based on the results of system monitoring, there is no need to do manual checking for suspicious transactions. The AML & CFT Officer will get an Alert or Notification to the Email automatically every day. So they can run the next process such as Enhanced Due Diligenced (EDD) to partners if any suspicious transaction found. It helps Financial Transaction Reporting and Analysis Center (FTRAC) for transactions of Suspected Terrorist Lists and Terrorist Organizations (STLTO), as well as the List of Anti-Money Laundering and Combating the Financing of Terrorism and the Proliferation of Weapons of Mass Destruction. (AML/CFTWMD)